Kinetics of Early Innate Immune Activation during HIV-1 Infection of Humanized Mice. - Skelton, Jessica Katy; Ortega-Prieto, Ana María; Kaye, Steve; Jimenez-Guardeño, Jose Manuel; Turner, Jane; Malim, Michael H.; Towers, Greg J.; Dorner, Marcus (ASM Journals, 2019)
Human immunodeficiency virus type 1 (HIV-1) infection is associated with aberrant immune activation; however, most model systems for HIV-1 have been used during established infection. Here, we utilize ultrasensitive HIV-1 quantification to delineate early events during the eclipse, burst, and chronic phases of HIV-1 infection in humanized mice. We show that very early in infection, HIV-1 suppresses peripheral type I interferon (IFN) and interferon-stimulated gene (ISG) responses, including the HIV-1 restriction factor IFI44. At the peak of innate immune activation, prior to CD4 T cell loss, HIV-1 infection differentially affects peripheral and lymphoid Toll-like receptor (TLR) expression profiles in T cells and macrophages. This results in a trend toward an altered activation of nuclear factor κB (NF-κB), TANK-binding kinase 1 (TBK1), and interferon regulatory factor 3 (IRF3). The subsequent type I and III IFN responses result in preferential induction of peripheral ISG responses. Following this initial innate immune activation, peripheral expression of the HIV-1 restriction factor SAM domain- and HD domain-containing protein 1 (SAMHD1) returns to levels below those observed in uninfected mice, suggesting that HIV-1 interferes with their basal expression. However, peripheral cells still retain their responsiveness to exogenous type I IFN, whereas splenic cells show a reduction in select ISGs in response to IFN. This demonstrates the highly dynamic nature of very early HIV-1 infection and suggests that blocks to the induction of HIV-1 restriction factors contribute to the establishment of viral persistence
Keywords: Virología - Investigación; Virus del SIDA; Modelos animales en investigación; SIDA - Modelos animales; Virology; Virus; HIV